Improving Logistics Distribution Through Transportation Infrastructure Development in Greater Jakarta - Susantono, Bambang; Berawi, Mohammed A.; Miraj, Perdana; Petroceany, Jade S. (CSID Journal of Infrastructure Development, 2015)
The Greater Jakarta Industrial Area is the biggest contributor of Indonesia’s exported goods, hence logistics distribution from and to this area are becoming increasingly critical. Tanjung Priok Port and Soekarno-Hatta Airport are two transport systems that support this area’s logistics distribution. However, problems including overcapacity of Tanjung Priok Port and Soekarno-Hatta Airport, as well as dependency on roads to transport cargo, lead to decrease national logistics performance. This paper presents a transportation infrastructure development scenario to support the logistics and supply chains of the Greater Jakarta Industrial Area, which will eventually raise the national competitiveness level to compete in the global and regional markets. The scenario will be developed based on various data analyses, including Greater Jakarta’s logistics data, as well as infrastructure capacity and predicted demand. Meanwhile, the transportation infrastructure would include the development of multiple-ports, multiple-airports, as well as road and railway connectivity.